Impact of Overfishing on Density and Test-Diameter Size of the Sea Urchin Tripneustes gratilla at Wakatobi Archipelago, South-Eastern Sulawesi, Indonesia - La Nane; Arfiani Rizki Paramata (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2020)
Sea urchin Tripneustes gratilla is one of an economically important fisheries resource product for localities at Wakatobi archipelago. High demands for sea urchin gonad have intensified high fishing activity. The hypothesis of this study is that sea urchins in Wakatobi have been overfished. To answer that hypothesis, the density and its test diameter size were measured at two different sites. Those two sites are Pulau Tomia (resident area) and Pulau Sawa (nonresident area and very distant from the localities). The results show that sea urchin density and its test diameter are significantly different.  The densities (mean±SE) T. gratilla at Pulau Sawa and Pulau Tomia were 10±0.6 (ind.m-2) and 2.7±0.9 ind.m-2, respectively. Moreover, the test diameter at Pulau Sawa and Pulau Tomia were 69.7±2.1 mm and 58.5±1.7 mm (mean±SE), respectively. These results have shown that overfishing has occurred. Therefore, sea urchin with test diameter 66–75 mm, 76–85 mm, and 86–95 mm have disappeared at Pulau Tomia. The Conclusion reveals that fishing of sea urchin Tripneustes gratilla at Pulau Tomia has been overfished.